Effective Approaches to Enhance Social Media Marketing for Philippine Small Enterprises - Santos, Angelo R.; Ortiz, Arjay F.; Fronda, Jennifer G.; Galano, Joannie A.; Savellano, Joy N. (International Review of Management and Marketing, 2024)
This study investigates the effectiveness of social media marketing for small businesses in San Isidro, Nueva Ecija. Using a descriptive quantitative research design, data were collected from 68 small business owners through structured questionnaires. The study evaluates how these businesses utilize social media platforms, the impact of their social media marketing efforts on business outcomes, and the challenges faced. Findings indicate that social media marketing significantly enhances brand awareness, customer engagement, and sales performance. Despite challenges such as limited financial resources and technical skills, small businesses can optimize their strategies through regular postings and interactive content. An action plan is proposed to address these challenges, including training programs, financial support, resource provision, ROI measurement tools, continuous learning, and technical support. The study highlights the potential of social media marketing to drive sustainable growth for small businesses in rural areas.